APPLICATIONS TO MONITOR MATERNAL HEALTH IN PREVENTING STUNTING - Riska Rosita; Tominanto Tominanto; Andi Yulianto (LPPM Universitas Duta Bangsa Surakarta, 2022)
Adequate nutrition during pregnancy affects the incidence of stunting. Every pregnant woman is encouraged to have regular prenatal checkups. But many pregnant women and nursing mothers do not routinely do checkups. They even lost a book to monitor Maternal and Child Health, so the examination history was not fully documented. This creates problems such as incomplete patient data, and midwives having difficulty finding patient history. The purpose of this study is to develop an application to monitor maternal health. Monitoring is also carried out to help detect early if there are potential abnormalities or health problems for the mother and fetus. The research method uses the Rapid Application Development (RAD) approach, by developing computer applications to monitor maternal health. The results show that this application can produce information on the history of physical examinations on patients more quickly and accurately. Reports are presented in the form of printouts and graphics. The graphic display makes it easier for the midwife to read the progress of the patient's health. Midwives are also faster in detecting abnormal patient conditions, so midwives can immediately provide education, action, or therapy.